2020
DOI: 10.3390/cancers12123712
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of SWI/SNF Inactivation in Lung Adenocarcinoma Cell Models

Abstract: Mammalian SWI/SNF (SWitch/Sucrose Non-Fermentable) complexes are ATP-dependent chromatin remodelers whose subunits have emerged among the most frequently mutated genes in cancer. Studying SWI/SNF function in cancer cell line models has unveiled vulnerabilities in SWI/SNF-mutant tumors that can lead to the discovery of new therapeutic drugs. However, choosing an appropriate cancer cell line model for SWI/SNF functional studies can be challenging because SWI/SNF subunits are frequently altered in cancer by vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…NGS studies have identified that the multiprotein complex SWI/SNF ( SWitch/Sucrose Non-Fermentable ) is mutated in almost 25% of human neoplasias [ 2 , 3 ]. Before the era of NGS, our group discovered that SMARCA4 is frequently inactivated by truncating mutations in LUAD [ 4 6 ]. Together with SMARCA4 , other SWI/SNF subunits, such as ARID1A , are recurrently mutated in LUAD and considered as LUAD driver genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS studies have identified that the multiprotein complex SWI/SNF ( SWitch/Sucrose Non-Fermentable ) is mutated in almost 25% of human neoplasias [ 2 , 3 ]. Before the era of NGS, our group discovered that SMARCA4 is frequently inactivated by truncating mutations in LUAD [ 4 6 ]. Together with SMARCA4 , other SWI/SNF subunits, such as ARID1A , are recurrently mutated in LUAD and considered as LUAD driver genes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together with SMARCA4 , other SWI/SNF subunits, such as ARID1A , are recurrently mutated in LUAD and considered as LUAD driver genes [ 7 ]. Recently, our group has shown that more than 76% of LUAD cell lines have at least one mutated SWI/SNF subunit [ 6 ]. However, the exact composition of the SWI/SNF complex in LUAD is currently unknown and we lack an integration of the genetic and transcriptional profile of this complex in order to facilitate a practical transfer to the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…SMARCA4 and SMARCA2 loss are the main immunohistochemical markers of SMARCA4‐dUT, although some SMARCA4‐deficient NSCLC tumors can also present these same features [5]. In our previous study of the SWI/SNF expression and mutational status on a panel of 38 LUAD cell lines, we discovered that three cell lines harbored SMARCA4 inactivating mutations, and they had a null expression of SMARCA2 : A427, NCI‐H23, and NCI‐H522 [7].…”
Section: Resultsmentioning
confidence: 99%
“…We recently characterized the mutational status and expression profile of 20 SWI/SNF members in 38 LUAD cell lines and tumor patient samples [7,8]. Because SMARCA4-dUT was just recently included in the 2021 WHO classification of lung tumors, there is a possibility that some of the cell lines previously classified as LUAD cell lines could now be better reinterpreted as SMARCA4-dUT.…”
Section: Introductionmentioning
confidence: 99%
“…Massive sequencing studies have revealed that SWI/SNF complexes are among the most recurrently mutated functional elements across all tumor types, reaching an overall mutation rate of 25% [ 7 ]. Mutations found in cancer-related SWI/SNF subunits are mostly deleterious [ 8 ], consistent with the widespread tumor suppressor function of the complex. Accordingly, sequencing studies in AML have also found tumor suppressor-like mutation patterns in SWI/SNF genes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 85%